Development and implementation of a tracer tool for infection prevention in clinical laboratory settings - Higgins, Kira (My University, 2025)
This Applied Practice Experience project was completed with the Infection Prevention and Control department at The University of Kansas Health System and focused on strengthening infection prevention practices within clinical laboratory settings. While the Infection Prevention and Control team routinely conducts tracers in patient-facing areas such as inpatient units, operating rooms, and outpatient clinics, laboratory environments had not previously been included in standardized audits. To address this gap, I independently designed and piloted a laboratory-specific tracer tool grounded in evidence-based guidelines from the Association for Professionals in Infection Control and Epidemiology, the Centers for Disease Control and Prevention, and The Joint Commission. By expanding tracer methodology to laboratory settings, this project supported a more comprehensive, population-level approach to infection prevention and healthcare quality assurance. The tool was implemented through direct observation of laboratory practices and structured staff engagement, with compliance documented using a standardized scoring system. Tracer data were analyzed by location and domain to identify both recurring patterns and site-specific issues. The tracer was piloted across three cancer center laboratories and assessed compliance in six domains: hand hygiene, personal protective equipment/staff safety, clean supply storage, soiled item management, environmental safety, and cleaning/disinfection. Findings highlighted strong performance in sharps safety, personal protective equipment availability, and disinfection practices, alongside recurring deficiencies in supply storage and hand hygiene. Site-specific issues, such as cluttered workspaces and improper sink use, were also identified. Results were communicated directly to laboratory leadership, with actionable recommendations provided to address areas of noncompliance. This integrative project applied foundational public health competencies in population-based project design, evaluation, data interpretation, leadership, and communication to address a systemic gap in infection prevention. The project strengthened laboratory safety by developing and implementing a sustainable tracer tool, while enhancing collaboration between Infection Prevention and Control and laboratory medicine. Laboratory safety supports infection control across healthcare systems by preventing cross-contamination and protecting vulnerable populations, such as immunocompromised cancer patients. In this way, the project not only contributed to system-wide quality improvement and compliance with external standards but also advanced the broader public health mission of reducing infection risk and strengthening healthcare capacity.
Keywords: infection prevention; laboratory safety; compliance; infection control